2018
DOI: 10.2174/1874613601812010162
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Hospitalised HIV/AIDS Patients in a Tertiary Centre in Sub-Saharan Africa: Trends Between 2007 and 2015, Causes and Associated Factors

Abstract: Background: With easy accessibility to combination Antiretroviral Therapy (cART), mortality amongst hospitalized HIV/AIDS patients needs to be described. Objective: We aimed at determining the trends, causes and factors associated with in-hospital mortality amongst HIV/AIDS patients in the Douala General Hospital. Methods: We retrospectively rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…This study found that patients whose CD4 cell count < 200cells/ mm3 had a higher risk of death compared to patients with a CD4 cell count ≥ 500cells/mm3. The study showed that the CD4 cell count was an independent predictor of AIDS progression, and was also consistent with the other research results done outside of Ethiopia [21], [22] which indicated that AIDS progression to death was clustered among patients starting therapy with a lower CD4 cell count. Thus, emphasizing the need to early diagnose, link, and engage patient into the comprehensive ART care program.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that patients whose CD4 cell count < 200cells/ mm3 had a higher risk of death compared to patients with a CD4 cell count ≥ 500cells/mm3. The study showed that the CD4 cell count was an independent predictor of AIDS progression, and was also consistent with the other research results done outside of Ethiopia [21], [22] which indicated that AIDS progression to death was clustered among patients starting therapy with a lower CD4 cell count. Thus, emphasizing the need to early diagnose, link, and engage patient into the comprehensive ART care program.…”
Section: Discussionsupporting
confidence: 91%
“…We demonstrated that patients whose CD4 cell count was <200 cells/mm3 had a higher risk of death compared to patients with a CD4 cell count ≥ of 500 cells/mm3. The study showed that the CD4 cell count was an independent predictor of AIDS progression, and it is a consistent finding with other research results conducted outside of Ethiopia [ 9 , 23 ] which indicated that AIDS progression to death was clustered among patients starting therapy with a lower CD4 cell count. Thus, emphasizing the need for early diagnosis, linking, and engaging patients in a comprehensive ART care program could help reduce mortality rates.…”
Section: Discussionsupporting
confidence: 90%
“…A viral load greater than 400 copies/mL, a CD4 count less than 200 cells/mL, TB coinfection, opportunistic infections, ART regimen, drug allergy, and low hemoglobin levels are predictors of mortality [6,7]. However, these are not the only factors that lead to HIV/AIDS mortality [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%